The relationship between SARS-CoV-2 neutralising antibody titres and avidity in plasma collected from convalescent non-vaccinated and vaccinated blood donors - Nurmi, Visa (2023)
Convalescent plasma (CP) treatment of COVID-19 has shown significant therapeutic effect when administered early (e.g. Argentinian trial showing reduced hospitalisation) but has in general been ineffective (e.g. REMAP-CAP trial without improvement during hospitalisation). To investigate whether the differences in CP used could explain the different outcomes, we compared neutralising antibodies, anti-spike IgG and avidity of CP used in the REMAP-CAP and Argentinian trials and in convalescent vaccinees. We found no difference between the trial plasmas emphasising initial patient serostatus as treatment efficacy predictor. By contrast, vaccinee convalescent plasma showed significantly higher titres and avidity, being preferable for future CP-treatment.